Asuhan Keperawatan Medikal Bedah Pada Pasien Dengan Pre Post Apendiktomi Diruangan Bedah Rumah Sakit Prof. H. M. Yamin S.H Pariaman - Wildatul Lara Husna; Aulia Asman; Kheniva Diah Anggita; Mike Asmaria (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Appendicitis is inflammation of the appendix caused by lumen obstruction, infection, or fecaliths, characterized by right lower abdominal pain, nausea, vomiting, and fever. The primary treatment for this condition is appendectomy. Globally, the incidence of appendicitis reaches around 214 per 100,000 population while the incidence of appendectomy is around 88%–90% of cases. At Prof. M. Yamin S,H Pariaman Regional General Hospital, Appendicitis was recorded in 80 cases with Appendectomy surgery in 37 cases. The purpose of writing this scientific paper is to provide nursing care to pre-post appendectomy patients in the Operating Room of Prof. M. Yamin S,H Pariaman Regional General Hospital. The method used is a case study carried out in the operating room for 6 days on February 7, 2026 to February 12, 2026 with a sample of Ms. Z. The results of the study obtained 6 Pre-Operative nursing problems, namely Acute Pain, Hyperthermia, Anxiety. And Post-Operative, namely Acute Pain, Impaired Physical Mobility, Risk of Infection. Nursing actions included monitoring vital signs, assessing pain levels, providing comfortable positions, deep breathing relaxation techniques, collaborative analgesic administration, aseptic surgical wound care, health education, and recommendations for gradual early mobilization. A 6-day evaluation showed that the nursing issues were resolved on the sixth day, with diagnoses of acute pain, impaired physical mobility, and risk of infection. The patient and family were advised to maintain wound hygiene, mobilize gradually, comply with treatment, and seek immediate medical attention if any signs of complications arise.